Kemampuan Siswa Kelas V SDN dalam Gugus 3 Kota Sabang Menulis Kembali Cerita Rakyat yang Dibaca - Mustika Sari; Mohd. Harun; Siti Sarah Fitriani (Center of Language and Cultural Studies, 2019)
This study aims at determining the ability of the fifth-grade students of state primary schools (SDNs) located in cluster 3 of Sabang City, Aceh; to rewrite folktales that are read, including the aspects of character, background, plot, language, and punctuation. The approach employed by this study is a descriptive quantitative approach. The population as well as samples in this study were 20 fifth-grade students of SDN 26 and 20 students of SDN 28 Sabang. The research data was collected by test techniques, in the form of assignments. Data is analyzed by quantitative descriptive analysis techniques, namely making a list of raw scores, calculating the average score of students, and classifying the results of the samples studied. The results of the study showed that the ability of the fifth grade students of SDNs in cluster 3 of Sabang City to rewrite the read folklore had not reached the specified value criteria. There are only 35% of students who have sufficient ability or score above 75, and many 65% of students do not have adequate ability who score below 75. This study also shows that of 40 students, only 3 students get a very good predicate with a score of 90, 30 students obtained a good predicate with a score of 65-85, and 7 students obtained a sufficient predicate with a score of 60.